Post-Conflict Cultural Revival and Social Restructuring in Northern Uganda - Erin Cagney (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
In northern Uganda, cultural revival has become a major topic of concern after the decades-long civil conflict that displaced 1.9 million people. During that time, the Lord’s Resistance Army (LRA) abducted an estimated 20,000 children and adults as mercenaries, porters, and sex slaves, and killed and mutilated thousands of others. The LRA wreaked general havoc on the entire northern population, contributing to the ensuing psychological and physical traumas that accompany such an experience. In the chaos and devastation of the protracted conflict, many cultural practices have fallen to the wayside, including dances, songs, folktales, marriage rites, social norms and rules, and the practice of wang’oo - nightly fireside meetings with extended family members. Wang’oo is seen by many to be the social, cultural, political, and ideological backbone of Luo society. Its discontinuation has led to the prolonged absence of other practices and has contributed to the general sense of social breakdown. In this thesis, I propose that the post-conflict reconstruction era in northern Uganda has opened up a space for social restructuring, including adding and discontinuing practices by certain groups (i.e., the youth or the cultural institution) and I will discuss how this restructuring has been problematized, namely by elders. Though some cultural revival projects are carried out by foreigners, here I focus on the Acholi opinion of cultural revival. I will explore how some cultural practices have changed over the course of the war and how reviving wang’oo is understood to help those affected by the conflict to find some sense of healing and closure. Such help, in the view of wang’oo proponents, includes resolving some of the tension between those who experienced the conflict differently and empowering communities to form their own economic endeavors and demand better services from their government. My analysis is based on original fieldwork carried out over the course of seven months in 2010. I conducted focus group discussions, individual interviews with women’s groups, politicians, religious leaders, traditional dance groups, and many others. I also observed multiple cultural events, including wang’oo and traditional dance as well as carried out two projects that involved the youth experience of culture in the post-conflict setting. All names have been changed to protect the confidentiality of participants, except where permission was explicitly given.
Keywords: Uganda; Conflict; Wang' oo; Culture